Moldova : Reports on the Observance of Standards and Codes on Accounting and Auditing, Update - World Bank (Washington, DC, 2014)
This assessment of accounting and auditing practices in Moldova is part of a joint initiative that is implemented by the World Bank and the International Monetary Fund to prepare Reports on the Observance of Standards and Codes (ROSC). The assessment focuses on the strengths and weaknesses of the accounting and auditing environment that influence the quality of corporate financial reporting, and includes a review of both statutory requirements and actual practice. It uses International Financial Reporting Standards (IFRS) and the International Standards on Auditing (ISA) as benchmarks and draws on international experience and good practices, as well as the European Union's acquis communautaire given Moldova's strategy of further integration with the European Union. In the medium term, improvement in Moldova's business environment is essential to put the country on a sustainable growth path. The strategic objective of this task is to support the Government in its efforts to improving the business environment in Moldova by contributing to an elevated level of competitiveness and productivity across the economy through business enterprises providing timely and reliable financial information, formulated according to internationally accepted standards, while also observing standards of governance that create confidence among local and foreign investors. These will enable companies to have greater access to finance, invest and increase their productivity. This assessment was drawn up at the request of the Government of Moldova and builds on the previous Accounting and Auditing ROSC that was prepared in 2004. The 2004 ROSC had the following objectives: (i) to spell out the ingredients of a good set of national accounting and auditing practices; (ii) to assess how Moldovan practices and its accounting profession perform relative to those practices; and (iii) to lay out the reforms needed to bring those practices and the profession into compliance with the generic model of good practices.